Upaya Meningkatkan Hasil Belajar Fiqih pada Materi Menginfaqkan Harta di Luar Zakat Melalui Strategi the Power of Two Siswa Kelas VIII MTs Jam’iyah Mahmudiyah Tanjung Pura - Khairuddin YM (Fakultas Syariah IAIN Laa Roiba Bogor, 2019)
The purpose of this paper is to find out whether there is an increase in fiqh learning outcomes through the implementation of the power of two strategy for class VIII students at MTs Jam'iyah Mahmudiyah Tanjung Pura. This research method is by using a classroom action research approach. The data obtained from research through observation, tests or by using other strategies. The conclusions that can be drawn from this paper are student responses after the implementation of The Power Of Two learning strategy about improving Fiqh teaching and learning outcomes in the material of raising assets outside zakat for class VIII students at MTs Jam'iyah Mahmudiyah Tanjung Pura at the pre-test stage with an average value class 57.93 with the number of students who completed as many as 6 people with a percentage of 20.68% and students who did not complete as many as 23 people with a percentage of 79.31%, then after applying the power of two strategy there was an increase in the first cycle as many as 17 students completed with a percentage of 58.62% and as many as 12 students did not complete with a percentage of 41.38%. Because it has not met the researcher's target, it is continued in the second cycle. In the second cycle, there was an increase of 25 students who completed with a percentage of 88.20% and as many as 4 students did not complete with a percentage of 13.80%. Keywords: Improvement, The Power Of Two Strategy, creativity, Fiqh pelajaran lessons